SEEING STUDENTS AS POTENTIAL CO-DEVELOPERS OF FUTURE HEALTHCARE SOLUTIONS PROVOKES AMBIVALENT REACTIONS - Cathrine Sand Nielsen; Tina Kramer (Universidade Feevale, 2019)
ABSTRACT The development of an efficient and highly specialised healthcare service has meant that patients are moved between units and sectors, and encounter staff from a number of different professions. Scandinavian patients criticise the lack of coherence in such transitions, and politicians are demanding the development of coherent care pathways for patients. This article discusses contradictions inherent in the fact that students are traditionally trained within mono-professional study programmes, even though in the future they will have to be able to create coherent pathways across the professions for patients within the healthcare system. Based on two longitudinal ethnographic studies, and using Critical Theory as a theoretical framework, this article shows how study programmes have the potential to make students co-creators of the healthcare system. These ethnographic studies focus on the profession-oriented learning context, following a specific project entitled 'InBetween'. InBetween is a collaborative healthcare training project, aiming to develop a course of study to strengthen interprofessional patient-centred skills. In mapping out this field, the research projects explore the development of InBetween and the associated processes of individual, interprofessional and (inter)organisational learning and competence development. Using empirical data as a point of departure, we chart the development of new interprofessional communities of practice across professions, units and sectors. This article shows how communities of supervisors and students manoeuvre among contradictions arising between traditional mono-professionalism and the new interprofessionalism. The key point of this article is how the lack of tolerance of ambivalence in the field poses an obstacle to changes in healthcare. Keywords: Interprofessional education. Healthcare. Interprofessional supervision. Innovative Curriculum. Ethnography. RESUMO O desenvolvimento de um serviço de saúde eficiente e altamente especializado fez com que os pacientes fossem deslocados entre unidades e setores e encontrassem funcionários de várias profissões diferentes. Os pacientes escandinavos criticam a falta de coerência em tais transições e os políticos estão exigindo o desenvolvimento de caminhos coerentes de atendimento para os pacientes. Este artigo discute as contradições inerentes ao fato de os estudantes serem tradicionalmente treinados em programas de estudo monoprofissionais, embora, no futuro, eles tenham que ser capazes de criar caminhos coerentes entre as profissões para os pacientes no sistema de saúde. Com base em dois estudos etnográficos longitudinais e usando a Teoria Crítica como referencial teórico, este artigo mostra como os programas de estudo têm o potencial de tornar os alunos co-criadores do sistema de saúde. Esses estudos etnográficos se concentram no contexto de aprendizado orientado para a profissão, seguindo um projeto específico intitulado "InBetween". O InBetween é um projeto colaborativo de treinamento em saúde, com o objetivo de desenvolver um curso de estudo para fortalecer as habilidades interprofissionais centradas no paciente. Ao mapear esse campo, os projetos de pesquisa exploram o desenvolvimento do InBetween e os processos associados de aprendizado individual, interprofissional e (inter) organizacional e desenvolvimento de competências. Utilizando dados empíricos como ponto de partida, traçamos o desenvolvimento de novas comunidades de prática interprofissionais entre profissões, unidades e setores. Este artigo mostra como as comunidades de supervisores e estudantes lidam com as contradições que surgem entre o monoprofissionalismo tradicional e o novo interprofissionalismo. O ponto principal deste artigo é como a falta de tolerância à ambivalência no campo coloca um obstáculo às mudanças na área da saúde. Palavras-chave: Educação interprofissional. Cuidados de saúde. Supervisão interprofissional. Currículo Inovador. Etnografia.